"In Ecostore We Trust": uncovering the symbolic meanings of sustainable products & their use in building consumers’ self-image - Soo, Samuel (Auckland University of Technology, 2011)
The purpose of this study was to explore the symbolic meanings consumers took from a brand of sustainable products. This interaction between consumer and product is modelled by McCracken’s (1986) model of symbolic meaning transfer, which served as the study’s lens of interpretation. The symbolic meanings of products are important as consumers use these to build their self-image. This transfer of symbolic meaning is completed through the act of consumption. The study looked to provide an understanding of the role of consumption in order to inform attempts to initiate a shift in cultural values towards consumption. The undertaking of this research is significant as it contributes to a greater understanding of the sociological and symbolic function in conceptualisations of sustainable consumption. This would help to inform solutions that improve the sustainability of modern consumption. The study interviewed seven consumers of Ecostore products, a brand of sustainable household cleaning and body care products. The questions in the interview were informed by the model of symbolic meaning transfer and sought to allow participants to tell their consumption stories and rituals of the product. Questions explored the actions that participants took with Ecostore-branded products. The data collected was analysed by way of thematic analysis. The findings uncovered symbolic meanings of virtue, personal and collective values, health and trust in Ecostore products. Participants used these symbolic meanings to create their self-image through the ritual of consuming them. These rituals included the actions of buying, using, gifting and the disposal of the product. The self-image that participants built expressed that they were virtuous, responsible, contributing and risk-adverse members of society. Further, the personal and collective values of participants could be expressed through the consumption of the product. This ability to build self-image from Ecostore products was important to consumers and contributed to their decision to select them over others. This study has contributed to knowledge in the area of sustainable consumption by highlighting the symbolic significance of the consumption practice in the context of sustainable products. The symbolic meanings identified could be reflected in new product development, marketing management and advertising communications. This could help to increase levels of the consumption of sustainable products.
Keywords: Sustainable consumption; Sustainability; Symbolic consumption; Thematic analysis; Consumption; Symbolic meaning transfer